Functional polyimide dielectrics : structure, properties, and applications - Zha, Jun-Wei (Wiley-VCH, 2025)
An of-the-moment discussion of the most cutting-edge research in the field of polyimide dielectrics In Functional Polyimide Dielectrics: Structure, Properties, and Applications, distinguished researcher Dr. Jun-Wei Zha delivers an up-to-date and authoritative discussion of the latest advancements in the application of polyimide dielectrics (PIDs) in electrical and electronic equipment. Readers will find coverage of the application of PIDs in aerospace, high-temperature energy storage capacitors, corona-resistant motors, new energy power equipment, packaging, and more. The book serves as a valuable reference for improving the performance and expanding the application of existing PIDs, as well as designing and developing new PIDs. It also provides a current overview of research and frontier applications that will prove useful to students and researchers from multiple disciplines. Functional Polyimide Dielectrics also contains: A thorough introduction to the different types of polyimide dielectrics, including their synthesis, composites & blends, processing-property relationships, processing strategies and technologies, properties and applications Comprehensive explorations of a wide range of PID applications in a variety of special applications, like energy storage, insulation, thermal conductivity, intelligence, and more Practical discussions of the environmental aspects of the technology, as well as life cycle assessment sustainable alternative possibilities Complete treatments of smart polyimide dielectrics Perfect for materials scientists, electronics engineers, polymer chemists, physicists, and mechanical engineers, Functional Polyimide Dielectrics: Structure, Properties, and Applications will also benefit professionals, engineers, and scientists working in the chemical industry.
Keywords: Dielectrics.; Polyimides.; elektronické knihy; electronic books